Financing Activities and Payout Policies of Entrepreneurial Firms: Empirical Evidence from Initial Public Offerings in Germany - Martin Seim; Wolfgang Bessler; Wolfgang Drobetz (Verein für Socialpolitik, 2010)
Entrepreneurial high-technology start-up firms usually need equity in order to finance their research, product development, and in particular growth opportunities due to new ideas and innovation. In an advanced stage they often require even larger financial resources and may raise equity by going public (IPO) and, if successful, by a seasoned equity offering (SEO) later on. If these are the typical financing stages then it is surprising when firms that just went public start paying dividends or even repurchase shares. For a sample of 245 IPOs in Germany that either issued additional equity or initiated a share repurchase program, we analyze the valuation effects and the factors that explain the magnitude of these returns. For repurchasing firms we find significantly positive announcement returns (9.23%) but no abnormal stock price performance thereafter. For seasoned equity offerings we find a long term negative per-formance for the year prior to the announcement (11.55%) which continues in the subsequent year (30.20%). For the 30 day period before the SEO, we observe, however, a strong outper-formance (7.63%) suggesting that management was able to time the market. In various probit models we provide strong evidence that the decision to engage in repurchase activities is ex-plained by free cash flow problems rather than by undervaluation signaling. Our finding for repurchase decisions, however, is in contrast to the explanation of the announcement effects. For SEOs we conclude that IPOs return to the equity market to finance further growth oppor-tunities. This is consistent with our evidence for the cross-sectional regressions and the probit analysis. Overall, the cash position and the cash flows from operations turn out to be pivotal for the decision to engage either in repurchasing shares or in issuing additional equity.
Keywords: G32; G35; G38; 330; Share Buybacks; SEOs; Valuation Effects; Initial Public Offerings